Rio de Janeiro and other palaeodrainages evidenced by the genetic structure of an Atlantic Forest catfish. (25th March 2021) - Lima, Sergio M. Q.; Berbel‐Filho, Waldir M.; Vilasboa, Anderson; Lazoski, Cristiano; de Assis Volpi, Thaís; Lazzarotto, Henrique; Russo, Claudia A. M.; Tatarenkov, Andrey; Avise, John C.; Solé‐Cava, Antônio M.
Abstract: Aim: The disjunct distributions of freshwater organisms along coastal drainages are usually explained by palaeodrainages formed during sea‐level retreats that connected currently isolated basins, or by river capture from tectonic adjustments between adjoining watersheds. We evaluate the relative importance of these events on the genetic variation of freshwater fishes inhabiting the Serra do Mar in eastern Brazil, a region with steep mountains and pronounced bays. Location: Coastal river drainages in southeastern Brazil. Taxon: Catfishes of the Trichomycterus alternatus group. Methods: We tested the effects of palaeolandscape connections (GIS‐reconstructed palaeodrainages and putative river captures) on the genetic structure (mitochondrial and nuclear markers) of T . alternatus from 15 drainages using phylogenetic reconstructions, lineage delimitation methods and analyses of molecular variance. Results: Trichomycterus alternatus is monophyletic and comprised of three main lineages: two restricted to the basin at its northernmost distribution and another broadly distributed to the south. In the latter, seven major cytb clades were geographically compatible with the eight palaeodrainages, with three incongruences matching river captures previously described for the Guanabara Bay (GB). Shared haplotypes among isolated rivers flowing into GB provide the first molecular evidence of the 'Rio de Janeiro' palaeoriver. Main conclusions: Dispersal via palaeorivers is an important process, but it is not enough to recover the most recent dispersive events. Therefore, integrating both palaeo‐riverine configuration (GIS‐based) and localized river captures (geological studies) is crucial to reveal the role of past geological and climatic events on the distribution of freshwater organisms. Taken together, these two factors significantly explained a high portion T. alternatus genetic structure along coastal drainages, revealing a palaeolandscape scenario that may have been used by other freshwater Atlantic Forest taxa.